Use of carbon monoxide and hydrogen by a bacteria–animal symbiosis from seagrass sediments. (23rd July 2015) - Kleiner, Manuel; Wentrup, Cecilia; Holler, Thomas; Lavik, Gaute; Harder, Jens; Lott, Christian; Littmann, Sten; Kuypers, Marcel M. M.; Dubilier, Nicole
Summary: The gutless marine worm O lavius algarvensis lives in symbiosis with chemosynthetic bacteria that provide nutrition by fixing carbon dioxide (CO2 ) into biomass using reduced sulfur compounds as energy sources. A recent metaproteomic analysis of the O . algarvensis symbiosis indicated that carbon monoxide (CO) and hydrogen (H2 ) might also be used as energy sources. We provide direct evidence that the O . algarvensis symbiosis consumes CO and H2 . Single cell imaging using nanoscale secondary ion mass spectrometry revealed that one of the symbionts, the γ3‐symbiont, uses the energy from CO oxidation to fix CO2 . Pore water analysis revealed considerable in‐situ concentrations of CO and H2 in the O . algarvensis environment, Mediterranean seagrass sediments. Pore water H2 concentrations (89–2147 nM) were up to two orders of magnitude higher than in seawater, and up to 36‐fold higher than previously known from shallow‐water marine sediments. Pore water CO concentrations (17–51 nM) were twice as high as in the overlying seawater (no literature data from other shallow‐water sediments are available for comparison). Ex‐situ incubation experiments showed that dead seagrass rhizomes produced large amounts of CO. CO production from decaying plant material could thus be a significant energy source for microbial primary production in seagrass sediments.